Problem-based learning and process modeling in teaching information systems (Research, Society and Development, 2020)
In active learning methodologies it is common to use problem solving as teaching strategies to promote meaningful learning. This article aims to verify the use of process modeling as a didactic resource in teaching based on problem-situation analysis, which require information systems solutions. This is a qualitative study based on a report of experience in an undergraduate discipline. The teaching strategy adopted in the course was based on the Problem Based Learning method. In this course, students analyze real problem situations, interacting with process users that require information systems solutions. An approach was used that involves modeling the current state of processes, identifying improvement points and proposing information systems solutions in modeling that represent the future state of processes. As a result of the study, some of the processes that were analyzed during the course are described. The study indicates the potential applicability of process modeling for problem situation analysis in undergraduate disciplines in different areas of knowledge.